Pedagogical strategy for the correction of language disability in preschool children - Elaine Álvarez Martínez; Félix Lázaro Huepp Ramos; Miladis Fornaris Méndez (Medisur)
Background: Language disability is a disorder that has a negative impact on child development, so its correction from an early age is imperative to ensure comprehensive development. For the logopedic care, the integrality of the actions that are developed is important, which must also involve the families. Objective: to expose the results of a pedagogical strategy for the correction of language disability in preschool children. Methods: intervention study, with a before and after design, which involved four children and their families, as well as speech therapists from the Pepín Salvat Ladrón de Guevara Special School for Children with Language and Communication Disorders, in the Santiago de Cuba municipality. In addition to observation, interviews, speech therapy exploration techniques and language diagnostic tests were used: First Word Inventory, Peabody Picture Vocabulary Test and the Spontaneous Language Assessment Test. Results: advances in children’s language development were evidenced, both from a qualitative and quantitative point of view. Likewise, a greater understanding and commitment of the families in complying with the guidelines received for the speech therapy care of their children was appreciated. Conclusion: the strategy designed for comprehensive attention to the language development of preschool children was effective. Its comprehensive approach, with the participation of families and specialists, guaranteed the success of the designed actions.